Coral cover a stronger driver of reef fish trophic biomass than fishing. Issue 1 (3rd October 2020) - Russ, Garry R.; Rizzari, Justin R.; Abesamis, Rene A.; Alcala, Angel C.
Abstract: An influential paradigm in coral reef ecology is that fishing causes trophic cascades through reef fish assemblages, resulting in reduced herbivory and thus benthic phase shifts from coral to algal dominance. Few long‐term field tests exist of how fishing affects the trophic structure of coral reef fish assemblages, and how such changes affect the benthos. Alternatively, benthic change itself may drive the trophic structure of reef fish assemblages. Reef fish trophic structure and benthic cover were quantified almost annually from 1983 to 2014 at two small Philippine islands (Apo, Sumilon). At each island a No‐Take Marine Reserve (NTMR) site and a site open to subsistence reef fishing were monitored. Thirteen trophic groups were identified. Large planktivores often accounted for >50% of assemblage biomass. Significant NTMR effects were detected at each island for total fish biomass, but for only 2 of 13 trophic components: generalist large predators and large planktivores. Fishing‐induced changes in biomass of these components had no effect on live hard coral (HC) cover. In contrast, HC cover affected biomass of 11 of 13 trophic components significantly. Positive associations with HC cover were detected for total fish biomass, generalist large predators, piscivores, obligate coral feeders, large planktivores, and small planktivores. Negative associations with HC cover were detected for large benthic foragers, detritivores, excavators, scrapers, and sand feeders. These associations of fish biomass to HC cover were most clear when environmental disturbances (e.g., coral bleaching, typhoons) reduced HC cover, often quickly (1–2 yr), and when HC recovered, often slowly (5–10 yr). As HC cover changed, the biomass of 11 trophic components of the fish assemblage changed. Benthic and fish assemblages were distinct at all sites from the outset, remaining so for 31 yr, despite differences in fishing pressure and disturbance history. HC cover alone explained ~30% of the variability in reef fish trophic structure, whereas fishing alone explained 24%. Furthermore, HC cover affected more trophic groups more strongly than fishing. Management of coral reefs must include measures to maintain coral reef habitats, not just measures to reduce fishing by NTMRs.